(untitled) (Research, Society and Development, 2021)
Objectives: To analyze the coping strategies in mental health used by the elderly in their daily lives evidenced in the scientific literature. Describe the coping strategies focused on problems. Identify coping strategies focused on emotion. Assess changes in coping strategies in the face of social isolation. Methods: Study of integrative literature review. The following databases were used: Medical Literature Analysisand Retrieval System Online (MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS) and Nursing Database (BDENF), through the Virtual Health Library (VHL). Scientific articles published from 2015 to 2020. The search for scientific articles was carried out in the months of September and October 2020. He was registered at the Coordination for Research, Extension and Graduate Studies, under process nº 028/2020. Results: After selection in the databases, 2243 articles related to the descriptors were found, using the inclusion criteria, only 298 articles were left. Made a very careful reading of them and discarding those that had no relation to the theme, totaling 13 articles. The results were organized using a table. Conclusion: Many coping strategies are used, the most used are those that reinforce ties with family members, rescue memories from the past and involve religious practices. With the pandemic caused by COVID-19, these coping strategies were adapted.